NASICON type medium-entropy oxide solid electrolyte and preparation method thereof
By doping titanium, hafnium and letetium at the Zr site, NASICON type medium entropy oxide solid electrolyte is prepared, which solves the problem of insufficient conductivity and stability of traditional NASICON materials, and achieves a solid sodium battery with high energy density and long cycle life.
Patent Information
- Application Number
- CN202411784452.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional NASICON materials still have room for improvement in conductivity and stability, and it is difficult to meet the needs of high energy density, long cycle life and high safety energy storage equipment.
By doping tetravalent elements (titanium and hafnium) and trivalent elements (lutetium) at the Zr site, NASICON type medium entropy oxide solid electrolyte is prepared, with the chemical formula Na3.5Zr0.5Ti0.5Hf0.5Lu0.5Si2PO12, improving its sodium ion conduction ability and chemical stability.
High ionic conductivity (7.2×10-4~9.3×10-4S cm-1) and good chemical stability are achieved, which significantly improves the cycle stability of solid sodium batteries.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a NASICON medium-entropy oxide solid electrolyte and a preparation method thereof. Background Art
[0002] With the increasing demand for high energy density, long cycle life and high safety energy storage devices, solid-state batteries have become a research hotspot due to their potential advantages. Solid electrolytes are key materials for solid-state batteries, and their performance directly affects the overall performance of the battery. At present, common solid electrolyte materials such as oxides, sulfides and polymers have some defects. For example, oxide and polymer solid electrolytes generally have low ionic conductivity, while sulfide solid electrolytes have poor chemical stability despite their high ionic conductivity. NASICON-type structural materials (sodium superionic conductors) have become an ideal solid electrolyte material due to their unique crystal structure, which can provide wider ion channels, high ionic conductivity and good chemical stability. However, there is still room for improvement in the conductivity and stability of traditional NASICON materials. Therefore, it is of great significance to develop NASICON-type oxide solid electrolyte materials with higher ionic conductivity and better chemical stability. Summary of the invention
[0003] The object of the present invention is to provide a NASICON-type intermediate entropy oxide solid electrolyte and a preparation method thereof. The NASICON-type intermediate entropy oxide solid electrolyte provided by the present invention not only has a pure phase structure, but also has excellent sodium ion conductivity, and can improve the cycle stability of a solid-state sodium battery.
[0004] A NASICON-type intermediate entropy oxide solid electrolyte with a chemical formula of Na m Zr n Ti x Hf y Lu z Si2PO 12 , 3.3≤m≤3.7, 0.4≤n,x,y,z≤0.6.
[0005] The ionic conductivity is 7.2×10 -4 ~9.3×10 -4 S cm -1 , relative density is 95~98%.
[0006] The method for preparing the above-mentioned solid electrolyte comprises the following steps: According to the stoichiometric ratio, a sodium source, a zirconium source, a titanium source, a hafnium source, a lutetium source, a silicon source and a phosphorus source are ball-milled to obtain a NASICON type intermediate entropy oxide solid electrolyte precursor powder; calcining the NASICON medium-entropy oxide solid electrolyte precursor powder to obtain a NASICON medium-entropy oxide solid electrolyte powder; The NASICON medium entropy oxide solid electrolyte powder and a binder are mixed and molded to obtain a NASICON medium entropy oxide solid electrolyte blank; The NASICON medium-entropy oxide solid electrolyte green body is sintered to obtain a NASICON medium-entropy oxide solid electrolyte.
[0007] The calcination temperature is 900-1200°C and the holding time is 8-12 h.
[0008] The molding pressure is 6-10 MPa, the molding temperature is room temperature, and the heat preservation and pressure holding time is 5-10 minutes.
[0009] The sintering temperature is 1100-1250°C, the holding time is 10-24 h, and the heating rate from room temperature to the sintering temperature is 2-5°C min -1 .
[0010] The present invention provides the use of the NASICON medium-entropy oxide solid electrolyte described in the above technical solution or the NASICON medium-entropy oxide solid electrolyte prepared by the preparation method described in the above technical solution in a solid-state sodium battery. Beneficial Effects
[0011] The present invention provides a NASICON medium entropy oxide solid electrolyte, the chemical formula of which is Na 3.5 Zr 0.5 Ti 0.5 Hf 0.5 Lu 0.5 Si2PO 12 The present invention is based on Na2Zr2Si2PO 12 The NASICON-type medium entropy oxide solid electrolyte was prepared by replacing Zr with an equal molar ratio at the Zr site of (NZSP), and the NASICON-type medium entropy oxide was prepared by doping the Zr site with tetravalent elements (titanium and hafnium) and trivalent elements (lutetium). 4+ The ionic radius is larger than that of Zr 4+ Slightly smaller, doping with Ti can increase the void fraction in the lattice, thereby improving the mobility of sodium ions. In addition, Ti 4+ With Zr 4+ With similar oxidation states and chemical properties, doping Ti at the Zr site does not lead to significant changes in the crystal structure; for Hf 4+ Elements, due to their interaction with Zr 4+ The ionic radius of Hf4+ The ion radius is slightly smaller), doping Hf can maintain the stability of the NASICON structure of the material, while improving the mechanical strength and chemical stability of the material; Lu 3+ Doping with Ti 3+ and Hf 4+ The doping is different. Because it is a trivalent element, it will produce oxygen vacancies, which will change the migration path of sodium ions and increase the ionic conductivity of the material. At the same time, Lu 3+ The ionic radius of Zr is small, and doping may 4+ The site produces large local stress, which may cause local lattice distortion, thus affecting the overall performance of the material. The results of the embodiment show that the relative density of the NASICON medium entropy oxide solid electrolyte provided by the present invention is 98%, which is much higher than the relative density of the NZSP solid electrolyte (80%), and the ionic conductivity is as high as 9.3×10 -4 S cm -1 The NASICON-type intermediate entropy oxide solid electrolyte showed no formation of any impurity phase in the XRD spectrum, showing good structural stability. The solid-state sodium battery based on the NASICON-type intermediate entropy oxide solid electrolyte showed excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 XRD diagrams of NASICON oxide solid electrolytes in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 2 XRD diagrams of NASICON oxide solid electrolytes in Example 1 and Comparative Example 1 of the present invention at different preparation temperatures; Figure 3 1 is an EIS graph of the NASICON-type oxide solid electrolyte in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention; Figure 4 1 and 2 are constant current charge and discharge diagrams of the NASICON oxide solid electrolyte symmetrical battery in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0013] The present invention provides a NASICON medium entropy oxide solid electrolyte, the chemical formula of which is Na 3.5 Zr 0.5 Ti 0.5 Hf 0.5 Lu 0.5 Si2PO 12 , the ionic conductivity is preferably 7.2×10 -4 ~9.3×10 -4 S cm -1, more preferably 8.2×10 -4 ~9.3×10 -4 S cm -1 , the relative density is preferably 95-98%. In the present invention, the relative density is measured with reference to the theoretical density of the substance.
[0014] The present invention provides a method for preparing the NASICON medium entropy oxide solid electrolyte described in the above technical solution, comprising the following steps: Ball milling a sodium source, a zirconium source, a titanium source, a hafnium source, a lutetium source, a silicon source and a phosphorus source to obtain a NASICON type intermediate entropy oxide solid electrolyte precursor powder; calcining the NASICON medium-entropy oxide solid electrolyte precursor powder to obtain a NASICON medium-entropy oxide solid electrolyte powder; The NASICON medium entropy oxide solid electrolyte powder and a binder are mixed and molded to obtain a NASICON medium entropy oxide solid electrolyte blank; The NASICON medium-entropy oxide solid electrolyte green body is sintered to obtain a NASICON medium-entropy oxide solid electrolyte.
[0015] The present invention ball-mills a sodium source, a zirconium source, a titanium source, a hafnium source, a lutetium source, a silicon source and a phosphorus source to obtain a NASICON type medium entropy oxide solid electrolyte precursor powder. In the present invention, the purity of the sodium source, zirconium source, titanium source, hafnium source, lutetium source, silicon source and phosphorus source is preferably above 99wt%. In the present invention, the sodium source is preferably sodium carbonate or sodium hydroxide; the zirconium source is preferably zirconium oxide; the titanium source is preferably titanium dioxide; the hafnium source is preferably hafnium oxide; the lutetium source is preferably lutetium oxide; the silicon source is preferably silicon dioxide; and the phosphorus source is preferably ammonium dihydrogen phosphate.
[0016] The present invention preferably follows Na 3.5 Zr 0.5 Ti 0.5 Hf 0.5 Lu 0.5 Si2PO 12 The raw materials are weighed in a stoichiometric ratio, and sodium carbonate and diammonium phosphate are each in excess of 10wt% to compensate for the volatilization of sodium and phosphorus at high temperature. In a specific embodiment of the present invention, the mass ratio of sodium carbonate, zirconium oxide, titanium dioxide, hafnium oxide, lutetium oxide, silicon dioxide and diammonium phosphate is 2.807:0.848:0.549:1.448:1.369:1.653:1.741.
[0017] In the present invention, the ball milling is preferably wet ball milling. In the present invention, the dispersant used in the wet ball milling preferably includes ethanol or isopropanol. In the present invention, the rotation speed of the ball milling is preferably 500-800 r min -1 ; The ball milling time is preferably 6 to 12 hours, more preferably 12 hours. In the present invention, the ball milling medium used in the ball milling is preferably zirconium beads. In the present invention, the mass ratio of the total mass of the sodium carbonate, zirconium oxide, titanium dioxide, hafnium oxide, lutetium oxide, silicon dioxide and ammonium dihydrogen phosphate to the mass ratio of the dispersant and the ball milling medium is preferably 1:2:6 to 10, more preferably 1:2:8.
[0018] In the present invention, the ball milling is preferably carried out in a polytetrafluoroethylene ball milling jar. In the present invention, the ball milling is preferably carried out in an intermittent alternating ball milling manner, and is preferably: firstly milling in a forward direction for 20 minutes, resting for 10 minutes, and then milling in a reverse direction for 20 minutes.
[0019] In the present invention, after the ball milling, the obtained slurry is preferably dried to obtain NASICON type medium entropy oxide solid electrolyte precursor powder. In the present invention, the drying temperature is preferably 80°C; and the drying time is preferably 12h.
[0020] After obtaining the NASICON medium entropy oxide solid electrolyte precursor powder, the present invention calcines the NASICON medium entropy oxide solid electrolyte precursor powder to obtain the NASICON medium entropy oxide solid electrolyte powder. In the present invention, the calcination temperature is 900-1200 ° C, and the holding time is 8-12 h. In the present invention, the heating rate from room temperature to the calcination temperature is 4-10 ° C min -1 , more preferably 5 ℃ min -1 In the present invention, the calcination atmosphere is preferably an air atmosphere.
[0021] In the present invention, the calcination is preferably carried out in an alumina crucible in a box furnace.
[0022] In the present invention, the calcination is preferably followed by cooling to room temperature to obtain a NASICON medium entropy oxide solid electrolyte powder. In the present invention, the cooling rate is preferably 5-10 °C min -1 , more preferably 10 ℃ min -1 .
[0023] In the present invention, the chemical formula of the NASICON medium entropy oxide solid electrolyte powder is Na 3.5 Zr 0.5 Ti 0.5 Hf 0.5 Lu 0.5Si2PO 12 In the present invention, the color of the NASICON medium entropy oxide solid electrolyte powder is white.
[0024] After obtaining the NASICON medium entropy oxide solid electrolyte powder, the present invention mixes the NASICON medium entropy oxide solid electrolyte powder and a binder, and performs molding to obtain a NASICON medium entropy oxide solid electrolyte blank. In the present invention, the binder is preferably a polyvinyl alcohol (PVA) solution. In the present invention, the concentration of the PVA solution is preferably 2 to 6wt%, more preferably 4wt%. In the present invention, the solvent of the PVA solution is preferably deionized water. In the present invention, the mixing of the NASICON medium entropy oxide solid electrolyte powder and the binder is preferably carried out under grinding conditions.
[0025] In the present invention, the molding is preferably cold isostatic pressing; the molding pressure is preferably 6-10 MPa, more preferably 8 MPa; the molding temperature is preferably room temperature, specifically preferably 25-30 °C; the insulation time is preferably 5-10 min. In the present invention, the molding is preferably carried out in a mold; the inner diameter of the mold is preferably 10 mm. In a specific embodiment of the present invention, the inner diameter of the mold is determined according to the size of the button battery shell.
[0026] After obtaining the NASICON medium entropy oxide solid electrolyte green body, the present invention sintered the NASICON medium entropy oxide solid electrolyte green body to obtain a NASICON medium entropy oxide solid electrolyte. In the present invention, the sintering temperature is preferably 1100-1250 ° C, more preferably 1150 ° C. The holding time is preferably 10-24 h, more preferably 12 h. In the present invention, the sintering atmosphere is preferably an air atmosphere.
[0027] In the present invention, the heating rate from room temperature to the sintering temperature is 2-5 °C min -1 , more preferably 3 ℃ min -1 .
[0028] In the present invention, the sintering is preferably carried out in an alumina crucible of a box furnace. In the sintering process, a layer of NASICON medium entropy oxide solid electrolyte powder is laid on the bottom of the alumina crucible, and a layer of NASICON medium entropy oxide solid electrolyte powder is covered on the surface of the NASICON medium entropy oxide solid electrolyte blank to prevent adhesion to the crucible wall. In the sintering process, the particles of the NASICON medium entropy oxide solid electrolyte grow and become dense.
[0029] In the present invention, the temperature is preferably lowered to room temperature after the sintering to obtain a NASICON medium entropy oxide solid electrolyte. In the present invention, the cooling rate is preferably 2-5 °C min -1 , more preferably 2 ℃ min -1 .
[0030] In the present invention, the color of the NASICON medium entropy oxide solid electrolyte is white.
[0031] The present invention provides the application of the NASICON medium entropy oxide solid electrolyte described in the above technical solution or the NASICON medium entropy oxide solid electrolyte prepared by the preparation method described in the above technical solution in a solid-state sodium battery. In the present invention, the application preferably includes: using the NASICON medium entropy oxide solid electrolyte described in the above technical solution as an electrolyte, and using a sodium-tin alloy as a symmetrical electrode, and assembling a button battery in a glove box filled with argon. In the present invention, the NASICON medium entropy oxide solid electrolyte is preferably pretreated first; the pretreatment preferably includes sandpaper polishing, ultrasonic cleaning and drying performed in sequence. In the present invention, the ultrasonic cleaning is preferably carried out in an ethanol solution; the mass concentration of the ethanol solution is preferably 99.5%. In the present invention, the time of the ultrasonic cleaning is preferably 30 to 60 s.
[0032] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0033] (1) Weigh 2.807 g sodium carbonate, 0.848 g zirconium oxide, 0.549 g titanium dioxide, 1.448 g hafnium oxide, 1.369 g lutetium oxide, 1.653 g silicon dioxide, and 1.741 g ammonium dihydrogen phosphate and place the above raw materials into a polytetrafluoroethylene ball mill. Add 21 mL of ethanol and 82 g of zirconium beads in a mass ratio of 1:2:8 between raw materials, ethanol, and ball milling medium zirconium beads. Mill the mixture on a planetary ball mill at a speed of 600 r min. -1 , the time is 12 h; the ball-milled slurry is placed in a forced air drying oven at 80 °C and dried for 12 h to obtain NASICON type medium entropy oxide solid electrolyte precursor powder; (2) The NASICON medium entropy oxide solid electrolyte precursor powder is placed in an alumina crucible and heated in a box furnace at 5 °C min -1The temperature was raised to 1100 °C at a heating rate of 10 °C min -1 The mixture is cooled to room temperature at a rate of , and a NASICON medium entropy oxide solid electrolyte powder is obtained; (3) Weighing 500 mg of the NASICON medium entropy oxide solid electrolyte powder into an agate mortar, adding 20 mg of a binder PVA solution (the solvent is deionized water, the concentration is 4 wt%), grinding evenly, pouring the mixed powder into a mold with an inner diameter of 10 mm, and maintaining the pressure at 25 ° C and 8 MPa for 10 min to obtain a NASICON medium entropy oxide solid electrolyte green body; (4) spreading a layer of NASICON medium entropy oxide solid electrolyte powder on the bottom of an alumina crucible, placing the NASICON medium entropy oxide solid electrolyte green sheet into the alumina crucible, covering the green sheet with the NASICON medium entropy oxide solid electrolyte powder, and heating the green sheet in a box furnace at 3 °C min -1 The heating rate was raised to 1150 °C and sintered for 12 h at 2 °C min -1 The temperature was cooled to room temperature at a rate of , and a NASICON medium entropy oxide solid electrolyte was obtained. The ionic conductivity of the NASICON medium entropy oxide solid electrolyte prepared in this embodiment is 9.3×10 -4 S cm -1 .
[0034] According to the above scheme, a NASICON-type intermediate entropy oxide solid electrolyte was prepared, and the phase structure of the NASICON-type intermediate entropy oxide solid electrolyte was tested by XRD. The room temperature impedance of the NASICON-type intermediate entropy oxide solid electrolyte was tested by an electrochemical workstation.
[0035] The NASICON medium entropy oxide solid electrolyte prepared in this example was polished with sandpaper, placed in an ethanol solution for ultrasonic cleaning for 30 s, and then dried; sodium-tin alloy was used as a symmetrical electrode and assembled into a button battery in an argon-filled glove box, and the cycle performance of the symmetrical battery was tested using a Xinwei test system. Example
[0036] (1) Weigh 1.808 g of sodium hydroxide, 0.723 g of zirconium oxide, 0.469 g of titanium dioxide, 1.236 g of hafnium oxide, 1.168 g of lutetium oxide, 1.411 g of silicon dioxide, and 1.486 g of ammonium dihydrogen phosphate, and pour the above raw materials into a polytetrafluoroethylene ball mill. Add 17 mL of ethanol and 66 g of zirconium beads according to the mass ratio of raw materials, ethanol, and ball milling medium zirconium beads of 1:2:8. Mill on a planetary ball mill at a speed of 600 r min. -1, the time is 12 h; the ball-milled slurry is placed in a forced air drying oven at 80 °C and dried for 12 h to obtain NASICON type medium entropy oxide solid electrolyte precursor powder; (2) The NASICON medium entropy oxide solid electrolyte precursor powder is placed in an alumina crucible and heated in a box furnace at 5 °C min -1 The temperature was raised to 1100 °C at a heating rate of 10 °C min -1 The mixture is cooled to room temperature at a rate of , and a NASICON medium entropy oxide solid electrolyte powder is obtained; (3) Weighing 500 mg of the NASICON medium entropy oxide solid electrolyte powder into an agate mortar, adding 20 mg of a binder PVA solution (the solvent is deionized water, the concentration is 4 wt%), grinding evenly, pouring the mixed powder into a mold with an inner diameter of 10 mm, and maintaining the pressure at 25 ° C and 8 MPa for 10 min to obtain a NASICON medium entropy oxide solid electrolyte green body; (4) spreading a layer of NASICON medium entropy oxide solid electrolyte powder on the bottom of an alumina crucible, placing the NASICON medium entropy oxide solid electrolyte green sheet into the alumina crucible, covering the green sheet with the NASICON medium entropy oxide solid electrolyte powder, and heating the green sheet in a box furnace at 3 °C min -1 The heating rate was raised to 1150 °C and sintered for 12 h at 2 °C min -1 The temperature was cooled to room temperature at a rate of , and a NASICON medium entropy oxide solid electrolyte was obtained. The ionic conductivity of the NASICON medium entropy oxide solid electrolyte prepared in this embodiment is 8.2×10 -4 S cm -1 .
[0037] According to the above scheme, a NASICON-type intermediate entropy oxide solid electrolyte was prepared, and the phase structure of the NASICON-type intermediate entropy oxide solid electrolyte was tested by XRD. The room temperature impedance of the NASICON-type intermediate entropy oxide solid electrolyte was tested by an electrochemical workstation.
[0038] The NASICON medium entropy oxide solid electrolyte prepared in this example was polished with sandpaper, placed in an ethanol solution for ultrasonic cleaning for 30 s, and then dried; sodium-tin alloy was used as a symmetrical electrode and assembled into a button battery in an argon-filled glove box, and the cycle performance of the symmetrical battery was tested using a Xinwei test system. Comparative Example 1 Preparation of Na2Zr2Si2PO 12 (NZSP) Solid Electrolyte (1) Weigh 2.730 g sodium carbonate, 3.847 g zirconium oxide, 1.876 g silicon dioxide, and 1.976 g ammonium dihydrogen phosphate and pour the above raw materials into a polytetrafluoroethylene ball mill. Add 21 mL of ethanol and 85 g of zirconium beads according to the mass ratio of raw materials, ethanol, and ball milling medium zirconium beads of 1:2:8. Mill on a planetary ball mill at a speed of 500 r min. -1 , the time is 12h; the ball-milled slurry is placed in a forced air drying oven at 80°C and dried for 12h to obtain NZSP solid electrolyte precursor powder; (2) The NZSP solid electrolyte precursor powder was placed in an alumina crucible and heated in a box furnace at 5 °C min -1 The temperature was raised to 900 °C at a heating rate of 10 °C min -1 The mixture was cooled to room temperature at a rate of , to obtain NZSP solid electrolyte powder; (3) Weigh 500 mg of the NZSP solid electrolyte powder into an agate mortar, add 20 mg of a binder PVA solution (the solvent is deionized water, the concentration is 4 wt%), grind evenly, pour the mixed powder into a mold with an inner diameter of 10 mm, and maintain the pressure at 25 ° C and 8 MPa for 10 min to obtain a NZSP solid electrolyte green body; (4) Spread a layer of NZSP solid electrolyte powder on the bottom of an alumina crucible, place the NZSP solid electrolyte green sheet into the alumina crucible, cover the green sheet with the NZSP solid electrolyte powder, and heat the green sheet in a box furnace at 3 °C min -1 The heating rate was increased to 1150 °C and sintered for 12 h at a rate of 2 °C min -1 The temperature was cooled to room temperature at a rate of , and a NZSP solid electrolyte was obtained. The ionic conductivity of the NZSP solid electrolyte prepared in this comparative example was 2.0×10 -4 S cm -1 .
[0039] The NZSP solid electrolyte was prepared according to the above scheme, the phase structure of the NZSP solid electrolyte was tested by XRD, and the room temperature impedance of the NZSP solid electrolyte was tested by an electrochemical workstation.
[0040] The NZSP solid electrolyte prepared in this example was polished with sandpaper, placed in an ethanol solution for ultrasonic cleaning for 30 s, and then dried; sodium-tin alloy was used as a symmetrical electrode and assembled into a button battery in an argon-filled glove box, and the cycle performance of the symmetrical battery was tested using a Xinwei test system. Comparative Example 2 Preparation of Na3Zr 1.0 Ti 0.5 Hf 0.5Si2PO 12 (NZTHSP) Solid Electrolyte (1) Weigh 2.639 g sodium carbonate, 1.859 g zirconium oxide, 0.603 g titanium dioxide, 1.589 g hafnium oxide, 1.814 g silicon dioxide, and 1.909 g ammonium dihydrogen phosphate and pour the above raw materials into a polytetrafluoroethylene ball mill. Add 21 mL of ethanol and 85 g of zirconium beads in a mass ratio of raw materials, ethanol, and ball milling medium zirconium beads of 1:2:8. Mill on a planetary ball mill at a speed of 500 r min. -1 , the time is 12 h; the ball-milled slurry is placed in a forced air drying oven at 80 °C and dried for 12 h to obtain NZTHSP solid electrolyte precursor powder; (2) The NZTHSP solid electrolyte precursor powder was placed in an alumina crucible and heated in a box furnace at 5°C min -1 The temperature was raised to 900 °C at a heating rate of 10 °C min -1 The mixture was cooled to room temperature at a rate of , to obtain NZTHSP solid electrolyte powder; (3) Weigh 500 mg of the NZTHSP solid electrolyte powder and pour it into an agate mortar, then add 20 mg of the binder PVA solution (the solvent is deionized water, the concentration is 4wt%), grind it evenly, pour the mixed powder into a mold with an inner diameter of 10 mm, and maintain the pressure at 25 ° C and 8 MPa for 10 min to obtain the NZTHSP solid electrolyte green body; (4) Spread a layer of NZTHSP solid electrolyte powder on the bottom of an alumina crucible, put the NZTHSP solid electrolyte green sheet into the alumina crucible, cover the green sheet with NZTHSP solid electrolyte powder, and heat the green sheet in a box furnace at 3 °C min -1 The heating rate was increased to 1150 °C and sintered for 12 h at a rate of 2 °C min -1 The ionic conductivity of the NZTHSP solid electrolyte prepared in this comparative example is 2.0×10 -4 S cm -1 .
[0041] The NZTHSP solid electrolyte was prepared according to the above scheme, the phase structure of the NZTHSP solid electrolyte was tested by XRD, and the room temperature impedance of the NZTHSP solid electrolyte was tested by an electrochemical workstation.
[0042] The NZTHSP solid electrolyte prepared in this example was polished with sandpaper, placed in an ethanol solution for ultrasonic cleaning for 30 s, and then dried; sodium-tin alloy was used as a symmetrical electrode and assembled into a button cell in an argon-filled glove box, and the cycle performance of the symmetrical cell was tested using a Xinwei test system. Test Results Figure 1 1 is the XRD diagram of the NASICON type oxide solid electrolyte in Example 1, Example 2, Comparative Example 1 and Comparative Example 2. Figure 1 It can be seen that both Example 1 and Example 2 can generate a pure phase NASICON structure.
[0043] Figure 2 1 is the XRD diagram of the NASICON oxide solid electrolyte in Example 1 and Comparative Example 1 at different preparation temperatures. Figure 2 It can be seen that Example 1 can generate a pure-phase NASICON structure at different preparation temperatures, indicating that the NASICON-type medium-entropy oxide solid electrolyte has strong structural stability.
[0044] Figure 3 1 is the EIS graph of the NASICON oxide solid electrolyte in Example 1, Example 2, Comparative Example 1 and Comparative Example 2. Figure 3 It can be seen that the impedance values of Example 1 and Example 2 are very small, indicating that the ionic conductivity of the NASICON medium entropy oxide solid electrolyte is high.
[0045] Figure 4 The constant current charge and discharge diagrams of the NASICON medium entropy oxide solid electrolyte symmetrical battery in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are shown. Figure 4 It can be seen that the electrochemical stability of Example 1 and Example 2 is better, indicating that the NASICON medium-entropy oxide solid electrolyte prepared by the present invention has better sodium dendrite inhibition ability.
[0046] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A NASICON medium entropy oxide solid electrolyte, characterized in that: The chemical formula is Na m Zr n Ti x Hf y Lu z Si2PO 12 ,3.3≤m≤3.7,0.4≤n,x,y,z≤0.
6.
2. The NASICON medium entropy oxide solid electrolyte according to claim 1, characterized in that: The ionic conductivity is 7.2×10 -4 ~9.3×10 -4 S cm -1 , relative density is 95~98%.
3. The method for preparing the solid electrolyte according to claim 1, characterized in that: The steps include: According to the stoichiometric ratio, a sodium source, a zirconium source, a titanium source, a hafnium source, a lutetium source, a silicon source and a phosphorus source are ball-milled to obtain a NASICON type intermediate entropy oxide solid electrolyte precursor powder; calcining the NASICON medium-entropy oxide solid electrolyte precursor powder to obtain a NASICON medium-entropy oxide solid electrolyte powder; The NASICON medium entropy oxide solid electrolyte powder and a binder are mixed and molded to obtain a NASICON medium entropy oxide solid electrolyte blank; The NASICON medium-entropy oxide solid electrolyte green body is sintered to obtain a NASICON medium-entropy oxide solid electrolyte.
4. The preparation method according to claim 3, characterized in that: The calcination temperature is 900-1200° C., and the heat preservation time is 8-12 hours.
5. The preparation method according to claim 3, characterized in that: The molding pressure is 6-10 MPa, the molding temperature is room temperature, and the heat preservation and pressure holding time is 5-10 minutes.
6. The preparation method according to claim 3, characterized in that: The sintering temperature is 1100-1250° C., and the heat preservation time is 10-24 hours.
7. The preparation method according to claim 6, characterized in that: The heating rate from room temperature to the sintering temperature is 2-5°C min -1 .
8. Use of the solid electrolyte according to claim 1 in a solid-state sodium battery.